PENINGKATAN KUALITAS PROGRAM PNF DAN PTK-PNF DI ERA OTONOMI DAERAH - Agus Sadid (JIV-Jurnal Ilmiah Visi, 2009)
Within last ten years, the Indonesian government has been implementing decentralization policy by giving autonomous authority to the regions to strengthen the local goverments and to develop their areas. The decentralization policy is expected to motivate the local government and people to accelerate the development including human resource development. This study aimed at describing how the decentralization and the autonomous authority effected the quality improvement of the non-formal education and the tutors at Learning Activity Center (LAC) in Sumbawa. Using qualitative approach, this research collected data by observation and interview to analyze qualitatively.The analysis concludes that there is no significant improvement of non-formal education program and personnel.Besides, the local governmentâ€™s policy does not encourage the development of non-formal education programs. Finally, it can be concluded that the existing autonomy does not stimulate the development of non-formal education and personnel.